Oil and Gas Production, Exports and Imports as Critical Business Internationalization Operations for companies in Globalization: An Analytical Approach - Anis Benabed (Ovidius University Annals: Economic Sciences Series, 2024)
This paper analyzes and presents oil and gas production, exports and imports as critical business operations in globalization and internationalization in a shape of an analytical approach. The research methodology began with a literature review to the research topic then there was a focus on data analysis and description by creating a business model and framework that illustrates the connection and the trajectory between the oil and gas industry and business internationalization. The main research question is “Are oil and gas production, exports and imports critical business internationalization operations?” Some of the results showed that the business internationalization strategy needs to meet the criteria and regulations of the oil and gas business from the country of origin to the country of destination. In conclusion, oil and gas remain powerful energy sources compared to renewables due to the beneficial use. There is always a huge connection between the oil and gas industry and the oil and gas business internationalization operation since production, exports and imports are important driving factors in international trade, business internationalization and globalization.